DAIRY CATTLE FARMERS’ BEHAVIOUR AND FACTORS AFFECTING THE EFFORT TO ENHANCE THE ECONOMIC OF SCALE AT GETASAN DISTRICT, SEMARANG REGENCY - Eddy, B.T.; Roessali, W.; Marzuki, S. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
The objectives of the research were to investigate the behavior of dairy farmers and factorsaffecting the effort to enhance the economic of scale. Survey was conducted on 75 dairy farmers atGetasan District, Semarang Regency. Samples were drawn in random from villages of Jetak, Batur andTajur, 25 farmers each. The data were analyzed by logit model regression, using 15 indicators ofbehavioural approach and socio-economic factors as predictors (independent variables) i.e. ages, formaleducation, family size, experience in cattle rearing, number of cattle raised, production of milk and landoccupation. The result showed that 40.04% of the farmers were good, 33.07% were moderate and20.89% were low risk takers. The farmers’ behaviour in enhancing economic of scale significantlyinfluenced by the farmers’ age, milk production and number of cattle reared. The odds ratio of ages,milk production and number of cattle reared were 0.93; 1.32 and 1.37, respectively. These valuesindicated that as values of ages increased as much as 1 year, the values of the willingness on risk takingwill decrease as much as 0.93 times; the values of milk production increase as much as 1 litre, the valuesof the willingness on risk taking will increase as much as 1.32 times; and the values of the number ofcattle increased as much as 1 AU, the values of the willingness on risk taking will increase as much as1.37 times.